RESEARCH ONLINE PURCASE OFFLINE: STUDYING CONSUMER BEHAVIOR IN PURCHASING FASHION AT JURAGAN MODE SHOP IN BENGKULU CITY - Intan Dea Pratiwi; Andi Azhar (Suluh Adiluhung Publisher (SAPub), 2025)
This research aims to understand consumer behavior in purchasing fashion products at Juragan Mode Shop Bengkulu City using the Research Online, Purchase Offline (ROPO) approach, as well as to explore the factors that influence consumer decisions in choosing to do product research online before shopping at physical stores. The method used in this research is phenomenology, which focuses on understanding the experiences and perceptions of consumers in interacting with these two channels. The results show that most consumers do product research first through the internet, especially through social media and e-commerce platforms, to get information about price, product variety, and quality. After obtaining sufficient information, they decide to visit Juragan Mode Shop to make a purchase directly. Factors that influence the purchase decision include more competitive prices, guaranteed product quality, and the convenience and experience of shopping in a physical store. This research provides insight into how consumers utilize the internet in influencing their purchasing decisions, as well as the importance of physical stores in reinforcing those decisions.